2011
DOI: 10.1016/j.rmed.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Serum and BALF YKL-40 levels are predictors of survival in idiopathic pulmonary fibrosis

Abstract: The - 329 polymorphism was associated with serum and BALF YKL-40 levels in IPF patients. High serum and BALF YKL-40 levels are associated with poor survival in IPF patients and could be useful prognostic markers for survival in IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 41 publications
9
88
2
Order By: Relevance
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which it may be involved in tissue fibrosis include mediating Th2 cell-IL-13 signaling pathways, inflammatory cell and fibroblast survival and proliferation, and alternative alveolar macrophage activation (48). YKL40 expression localizes to bronchiolar epithelial cells and alveolar macrophages adjacent to fibrotic areas in IPF, and protein levels are elevated in the BALF and serum of patients with IPF compared with healthy controls (25,42). Elevated serum concentrations correlate with worse gas exchange (25), and in a small single-center study both BALF and serum levels were associated with survival in IPF (42).…”
Section: Core Pathway 2: Immune Dysregulationmentioning
confidence: 99%
“…They followed the patients for .4 years and found that combining serum and BALF levels of YKL-40 allowed for stratification by mortality, with those patients having higher levels in both serum and BALF demonstrating increased mortality. 82 Finally, a recent study of 315 patients with various ILDs, including 185 with IPF, determined significant elevations of YKL-40 in all ILDs compared to the control population, with the highest levels noted in NSIP, IPF, and COP. 83 While the biomarker does not appear to have any role in diagnosis, a subset of the study with available serial follow-up did find levels of YKL-40 decreased over time in COP, a disease which tends to respond to available therapies, while remaining consistently elevated in IPF patients, suggesting a possible role in evaluating disease activity and therapeutic monitoring.…”
Section: Ykl-40mentioning
confidence: 99%